THE INFLUENCE OF INDUSTRIAL EFFLUENT ON CHALLAWA RIVER WATER QUALITY - Abdulsalam, A.; Mohammed, Dahiru; Kwajaffa, H. M. (FUDMA JOURNAL OF SCIENCES, 2023)
Water from River Challawa was assessed to test  the influence of  industrial effluent on the quality of water from the river. Sample collection was done in the month of June, 2023 at the end of dry season. At each sampling three (3) samples were collected to ensure accuracy by replication. A total of twenty-seven samples (27) were collected. Descriptive statistics was carried out on the data. The results obtained were compared with FEPA and WHO standards. A paired sample t-test was also carried out to test for any significant difference in the mean value of parameters upstream and downstream of points of discharge of effluents. Based on the findings of the research, it was concluded that, BOD, TDS and EC at the effluent point before and after have no any significant effect on the quality water from Challawa River. The findings of the study also revealed absence of lead and low concentration of zinc in the water. It was recommended that, the water from River Challawa can be used for irrigation with good management practices.
Keywords: industrial effluent; water quality; River Challawa